Second-Generation Cephalosporins-Associated Drug-Induced Liver Disease: A Study in VigiBase with a Focus on the Elderly - Mariana Sipos; Andreea Farcas; Daniel Corneliu Leucuta; Camelia Bucsa; Madalina Huruba; Cristina Mogosan (MDPI AG, 2021)
Background: The objective of this study was to characterize individual case safety reports (ICSRs) and adverse drug reactions (ADRs) related to second-generation cephalosporins and resulting in hepatobiliary disorders, in VigiBase, WHO global database. Methods: All second-generation cephalosporins hepatobiliary ADRs reported up to July 2019 were included. Characteristic of cephalosporins and ADRs, aside from disproportionality data were evaluated. Results: A total of 1343 ICSRs containing 1585 ADRs were analyzed. Cefuroxime was suspected to have caused hepatobiliary disorders in most cases-in 38% of adults and in 35% of elderly. Abnormal hepatic function was the most frequent ADR, followed by jaundice and hepatitis. For 49% of the ADRs reported in the elderly and 51% in the adult population, the outcome was favorable, with fatal outcome for 2% of the adults and 10% of the elderly. Higher proportional reporting ration (PRR) values were reported in the elderly for cefotetan-associated jaundice, cefuroxime-associated acute hepatitis and hepatitis cholestatic as well as for cefotiam and cefmetazole-associated liver disorder. Conclusion: Hepatobiliary ADRs were reported for 2nd generation cephalosporins, with over 50% of cases in adults, without gender differences. Cholestatic hepatitis was predominately reported in the elderly and this category was more prone to specific hepatic reactions.